2007
DOI: 10.1002/path.2128
|View full text |Cite
|
Sign up to set email alerts
|

An oncogenetic tree model in gastrointestinal stromal tumours (GISTs) identifies different pathways of cytogenetic evolution with prognostic implications

Abstract: To model the cytogenetic evolution in gastrointestinal stromal tumour (GIST), an oncogenetic tree model was reconstructed using comparative genomic hybridization data from 203 primary GISTs (116 gastric and 87 intestinal GISTs, including 151 newly analysed cases), with follow-up available in 173 cases (mean 40 months; maximum 133 months). The oncogenetic tree model identified three major cytogenetic pathways: one initiated by -14q, one by -1p, and another by -22q. The -14q pathway mainly characterized gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
1
12

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 34 publications
10
105
1
12
Order By: Relevance
“…37,43,85,86,89,91 Losses on chromosomes 1p, 9p, 11p, and 17p are successively less common than 14q and 22q losses, but are more significantly associated with malignancy ( Figure 4). 37,43,85,89,[91][92][93][94] Losses on chromosomes 10, 13q, and 15q have also been reported in GISTs. 43,91 Gains on chromosomes 8q (including MYC), 3q (including SMARCA3), and 17q are associated with metastatic behavior.…”
Section: Micro-gistsmentioning
confidence: 99%
See 1 more Smart Citation
“…37,43,85,86,89,91 Losses on chromosomes 1p, 9p, 11p, and 17p are successively less common than 14q and 22q losses, but are more significantly associated with malignancy ( Figure 4). 37,43,85,89,[91][92][93][94] Losses on chromosomes 10, 13q, and 15q have also been reported in GISTs. 43,91 Gains on chromosomes 8q (including MYC), 3q (including SMARCA3), and 17q are associated with metastatic behavior.…”
Section: Micro-gistsmentioning
confidence: 99%
“…37,43,85,89,[91][92][93][94] Losses on chromosomes 10, 13q, and 15q have also been reported in GISTs. 43,91 Gains on chromosomes 8q (including MYC), 3q (including SMARCA3), and 17q are associated with metastatic behavior. 86,95 In a recent array-based analysis of gene copy number in 42 GISTs (23 with recurrence or metastasis), the tumors were separated into four groups reflecting their accumulated chromosomal changes.…”
Section: Micro-gistsmentioning
confidence: 99%
“…This suggests that these genetics aberrations may be important in both early tumor development and progression. [8][9][10][11][12][13][14][15][16][17][18][19][20] Gunawan et al 8 have recently proposed an oncogenetic tree model identifying three major cytogenetic pathways in 203 primary GISTs: one initiated by À14q, one by À1p and another by À22q, with different biologic and clinical behavior. GISTs involving the À14q pathway were predominantly gastric tumors with stable karyotype and more favorable clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…These chromosomal losses may represent an underlying pathogenetic event resulting in the inactivation or haploinsufficiency of tumor suppressor genes. [8][9][10][11][12][13][14][15][16][17][18][19][20] However, the biologic significance of these genetic alterations, as well as their clinical implications, remains unknown. To address this issue, we performed an integrative analysis of gene expression profiling and high-resolution genomic copy number in 25 GIST samples to investigate the relationship between karyotype and gene expression profile, and to identify new haploinsufficient tumor suppressor genes involved in GIST pathogenesis and tumor progression.…”
mentioning
confidence: 99%
“…Tibes et al [24] reported increased levels of phosho-extracellular signal regulated kinase 1/2 and phospho-AKT (Thr-308) but also of phospho-mTOR (Ser-2448) in acute myeloid leukemia. Another study showed that in 70% of gastrointestinal stromal tumors (GISTs), a loss of chromosome 14q encoding AKT1 is observed [28]. Subsequent qRT-PCR and RPPAbased experiments revealed a reduced expression of AKT1 protein in line with the heterozygous loss but a slightly increased abundance of phospho-AKT ( Fig.…”
Section: Quantitative Analysis Of Signaling Pathways In Tumorsmentioning
confidence: 95%